On \((1, 2)^\star\)-\(\check{g}_α\)-closed Sets - Ponmalar, A.; Asokan, R.; Nethaji, O. (Communications in Mathematics and Applications, 2021)
We introduce a new class of sets namely \((1, 2)^\star\)-\(\check{g}_α\)-closed sets, \((1, 2)^\star\)-\(Λ_{\mathcal{G}}\)-set, \((1, 2)^\star\)-\(λ_{\mathcal{G}}\)-set and \((1, 2)^\star\)-\(\check{g}_α\)-Locally closed sets are study in bitopological spaces. We prove that this classes lies between \((1, 2)^\star\)-\(α\)-closed sets and \((1, 2)^\star\)-\(α g\)-closed sets. Furthermore, we discuss some essential properties of \((1, 2)^\star\)-\(\check{g}_α\)-closed sets in present of this paper.
Keywords: \((1, 2)^\star\)-\(\check{g}_α\)-closed sets; \((1, 2)^\star\)-\(\mathcal{G}\)-\(\ker(A)\); \((1, 2)^\star\)-\(Λ_{\mathcal{G}}\)-set; \((1, 2)^\star\)-\(λ_{\mathcal{G}}\)-set and \((1, 2)^\star\)-\(\check{g}_α\)-LC